(3QYGjI cHGQ GdSf aj Ohd eLdS GdJYGhf GdNdjLj (B:s (3MbGFb hCQbGe (B/s - (3eLdS hRQGA GdYed hGdTDhf GdGLJeGYjI HOhd eLdS GdJYGhf dOhd GdNdjL GdYQHjI (B((3GdefGeI(B).s (3GdecJH GdJfajPjs ((3GdefGeI (B:s (3eLdS hRQGA GdYed hGdTDhf GdGLJeGYjI HOhd eLdS GdJYGhf dOhd GdNdjL GdYQHjI, GdecJH GdJfajPj,s, 1999)
(3JMJd aFI cHGQ GdSf aj eLJeYfG GdYQHj GdNdjLj hVYG GLJeGYjG eejRG hdgG ecGfI HGQRI heQehbI aj GdeMjW GdYGFdj eSJeOI ef eHGOF GdTQjYI GdESdGejI GdSeMGA hef ehQhK Gdbje hGdJbGdjO GdYQHjI GdCUjdI, MjK dG JRGd GdCSQI JJeSc HOhQgG GdEfSGfj hGdCNdGbj hGdOjfj aj QYGjI CaQGOgG GdeSfjf hJMjWge Hcd eXGgQ GdJbOjQ hGdeMHI hGdGMJQGe QZe GdJZjQGJ GdYejbI GdJj dMbJ HcjGf GdCSQI hhXGFagG heSDhdjGJgG HMce GdJMhdGJ GdeSJLOI GdJj CUGHJ WHjYI GdMjGI GdeYGUQI(B.s
(3UOQ HefGSHI GdSfI GdOhdjI dcHGQ GdSf (B1999.s
Keywords: (3GdeSfhfs -- (3QYGjIs -- (3Ohd GdNdjL GdYQHjIs -- (3EMUGAGJs; (3GdeSfhfs -- (3QYGjIs -- (3Ohd GdNdjL GdYQHjIs -- (3EMUGAGJs